If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -1 = 11 + 5 Reorder the terms: -1 + 6x = 11 + 5 Combine like terms: 11 + 5 = 16 -1 + 6x = 16 Solving -1 + 6x = 16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 6x = 16 + 1 Combine like terms: -1 + 1 = 0 0 + 6x = 16 + 1 6x = 16 + 1 Combine like terms: 16 + 1 = 17 6x = 17 Divide each side by '6'. x = 2.833333333 Simplifying x = 2.833333333
| X-3=3+3x | | 4/5p=3 | | -5(3+r)=30 | | -6.8+4.24=x | | y=1/3x1-2 | | 6(x+3)+8=-16 | | 28x+x+25*32= | | 3t-14t-4=18 | | (3x+5)(2x-1)=x(6x+1)-16 | | x=40.8 | | 20x-7=5+17x | | 7+2p=x | | 7+2p= | | xy+18=32 | | 8x-16=12x+32 | | 28x+x+25= | | 7x+3(4x-13)=189 | | 28x+x= | | 0.11x+0.12(900-x)=100 | | x+4y=23 | | 3x^3-21x^2-24x=0 | | x+3=-6x+3-6x | | Z^2-4iz-3=0 | | .35x+.50y=29 | | 2/5y-5=11 | | 3x^3+6x^2+24=0 | | 2x-22=6(x+3) | | m-41=x | | 1/2(8-c) | | 3x-(22)=-8 | | 2(x+6)=11(x-1/8) | | 7x^2-3x=6x |